2007
DOI: 10.2223/jped.1672
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in the treatment of children with phenylketonuria

Abstract: ResumoObjetivo: Avaliar o efeito do leite materno como fonte de fenilalanina (phe) nos níveis sangüíneos desse aminoácido e no crescimento de fenilcetonúricos. Métodos:Foram estudados 35 fenilcetonúricos que mantiveram leite materno, e os resultados foram comparados com os de 35 lactentes que usaram fórmula láctea comercial. Os grupos foram pareados por sexo e por idade à suspensão do aleitamento materno. Os dados foram analisados até a suspensão do leite materno ou durante 12 meses de acompanhamento. O grupo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 9 publications
1
31
0
2
Order By: Relevance
“…Almost 70% of mothers (n = 48) met the American Academy of Pediatrics 29 31 In this sample, mothers' with infants who have PKU from the United States and Canada on average breastfed longer than mothers with infants who have PKU from other countries in Europe, Asia, and South America reported by other investigators. 3,10,11,[15][16][17] Those studies consistently reported that the majority of mothers who were breastfeeding infants with PKU did not persist as long as mothers' breastfeeding healthy infants without PKU. Given that statistics for the incidence and duration of breastfeeding infants with PKU from countries outside North America are at least a decade old, current data might reveal more similar rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Almost 70% of mothers (n = 48) met the American Academy of Pediatrics 29 31 In this sample, mothers' with infants who have PKU from the United States and Canada on average breastfed longer than mothers with infants who have PKU from other countries in Europe, Asia, and South America reported by other investigators. 3,10,11,[15][16][17] Those studies consistently reported that the majority of mothers who were breastfeeding infants with PKU did not persist as long as mothers' breastfeeding healthy infants without PKU. Given that statistics for the incidence and duration of breastfeeding infants with PKU from countries outside North America are at least a decade old, current data might reveal more similar rates.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, comparison of Phe levels between breastfed and formula-fed infants with PKU was not conducted. Previous studies 2,3,[8][9][10][11]18 have consistently reported that breastmilk supplemented with Phe-free medical beverage is an acceptable dietary treatment for infants with PKU as Phe levels could be maintained within the desired range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, in the treatment of PKU, breastfeeding (BF) is suspended and the phenylalanine needed is provided through commercial milk-based formula, which amino-acid concentration is known. The amount of formula is determined by blood phenylalanine levels and varies according to the tolerance of each individual to the intake of this amino-acid (5)(6)(7) . The suspension of BF would be necessary because of the difficulty to quantify the intake of phenylalanine during BF, which could cause a wide variation in blood levels and/or keep its concentration at levels above those recommended, incompatible with proper treatment (8)(9)(10) to prevent sequelae.…”
Section: Introductionmentioning
confidence: 99%